Food web structure and variation in the Gila river, USA - Pilger, Tyler Jess (Kansas State University, 2009)
The upper Gila River basin in southwest New Mexico, USA is one of the few unimpounded drainage basins in North America and is a stronghold for the unique and endemic fishes west of the Continental Divide. Multiple non-indigenous fishes have been introduced to the Gila River and are a potential threat to native fishes, yet very little is known of the trophic ecology of the native and nonnative fishes. We used diet and stable isotopes collected from native and nonnative fishes to identify their trophic relationships and evaluate potential interactions in the upper Gila River basin during June-July, 2007 and 2008. Diet and stable isotope data indicated aquatic invertebrates were the primary food for both native and nonnative fishes. Native large-bodied fishes were mainly algivore/detritivores and native small-bodied fishes were primarily insectivores. Small-bodied nonnative fishes fed on detritus and aquatic invertebrates. Nonnative predators preyed on small-bodied fishes and predaceous aquatic invertebrates and had higher trophic positions than all native fishes. Although nonnative predators did not rely exclusively on native fishes as prey, their presence extended community food-chain lengths, and the combined predation on juvenile native fishes by multiple apex predators may threaten persistence of native fishes. The lack of concise evidence for negative effects suggested that impacts of nonnative predators were more subtle and confirmed the underlying complexity of a relatively simple community The extensive database on feeding relations of Gila River fishes allowed us to further understand how energy moves through ecosystems. Specifically, the goal of chapter two was to characterize variation in fish-community food web structure within and among study reaches on the Gila River using [superscript]13C and [superscript]15N stable isotopes. We hypothesized that food web structure would reflect variation in fish community structure, resource availability and environmental conditions across habitats. Food web structure in isotope bi-plot space was estimated using community-wide measures of trophic structure, mean trophic position, and food-chain length. Permutational multivariate analysis of variance indicated that indices of food web structure were more variable among than within reaches and this pattern was primarily associated with variation in trophicl area occupied by taxa in isotope bi-plot space and mean trophic position of those taxa. Variation in food web structure was significantly associated with fish species richness across macrohabitats but was weakly associated with abiotic reach-scale factors. Variation in food web structure was concordant with variation in fish community composition and suggested that factors influencing the distribution of fishes also influence food web structure.
Keywords: Gila River; Native fish conservation; Stable isotope analysis; Introduced species; Biology, Ecology (0329)